2015
DOI: 10.1186/s12885-015-1134-z
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Nrf2 attenuates Carmustine-induced cytotoxicity in U87MG human glioma cells

Abstract: BackgroundMalignant glioma is one of the most devastating tumors in adults with poor patient prognosis. Notably, glioma often exhibits resistance to conventional chemotherapeutic approaches, complicating patient treatments. However, the molecular mediators involved in tumor chemoresistance remain poorly defined, creating a barrier to the successful management of glioma. In the present study, we hypothesized that the antioxidant transcription factor, Nrf2 (nuclear factor erythroid-derived 2 like 2), attenuates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 51 publications
(46 reference statements)
1
11
0
1
Order By: Relevance
“…In addition, a significant negative correlation has been found between Nrf2 expression and the outcome for GBM patients [ 114 ]. Recent studies have reported that development of chemoresistance is associated with the constitutive activation of the Nrf2-mediated signaling pathway in many types of cancer cells, including gliomas [ 115 ]. Chrysin, a potent Nrf2 inhibitor, could effectively reverse the resistance of an anticancer drug by down-regulating the PI3K/Akt and ERK pathways [ 116 ].…”
Section: Nuclear Factor E2-related Factor 2 Inhibitionmentioning
confidence: 99%
“…In addition, a significant negative correlation has been found between Nrf2 expression and the outcome for GBM patients [ 114 ]. Recent studies have reported that development of chemoresistance is associated with the constitutive activation of the Nrf2-mediated signaling pathway in many types of cancer cells, including gliomas [ 115 ]. Chrysin, a potent Nrf2 inhibitor, could effectively reverse the resistance of an anticancer drug by down-regulating the PI3K/Akt and ERK pathways [ 116 ].…”
Section: Nuclear Factor E2-related Factor 2 Inhibitionmentioning
confidence: 99%
“…The overall median survival for patients with glioma is between 16 to 18 months (3,4). Notable advances in the therapeutic strategies of glioma have been made in the last decade, including neurosurgical approaches, chemotherapy and radiotherapy; however, the prognosis of glioma remains poor, mainly due to the fact that glioma cells are highly aggressive and capable of infiltrating adjacent normal brain tissue, leading to the failure of complete dissection of the tumor by surgery in the brain (5,6). Recurrence and resistance to chemotherapy are another two influential factors responsible for poor prognosis (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay (Promega Corp., Pittsburgh, PA, USA) was used to measure cell growth abilities according to the manufacturer's protocol. Briefly, U251 and U87 cells were seeded in 96-well plates at an initial density of 5x10 3 /well in DMEM supplemented with 10% FBS in a humidified incubator containing 5% CO 2 . Each experimental group of cells was spread into six wells and the cultural medium was replaced every other day.…”
Section: Methodsmentioning
confidence: 99%
“…According to a population-based investigation, the overall median survival duration for patients with malignant glioma is ~15 months (2). Despite significant advances in the therapeutic strategies of glioma, including neurosurgical approaches, chemotherapy and radiotherapy, the prognosis of patients with malignant glioma remains poor, primarily due to the fact that malignant glioma cells are highly aggressive and capable of infiltrating into adjacent normal brain tissue, leading to the eventual failure of complete surgical dissection of the tumor (3,4). Recurrence and resistance to chemotherapy are to be claimed two influential factors for prognosis (5,6).…”
Section: Introductionmentioning
confidence: 99%